Evaluation of diagnostic tests, clinical and histopathological findings with Helicobacter pylori infection in pediatrics - Burcu Güven; Hacer Fulya Gülerman; Birgül Kaçmaz (Van Tıp Dergisi, 2019)
INTRODUCTION: Although severe diseases are seen in adults, Helicobacter pylori (H.pylori) infection is usually acquired during childhood. Because of that, it is more important to diagnose H. pylori infection in children correctly. The objective of this study to evaluate age, gender, diagnostic tests, clinical and histopathological findings with H.pylori infection in pediatrics. METHODS: Retrospectively, pediatric patients applied upper gastrointestinal endoscopy and detected H.pylori infection, were evaluated according age, gender, complaints, fecal H.pylori antigen and histopathological findings. RESULTS: The mean age of study population was 14.2 years (Range 1-18 years), median 15 years; 75% (111/148) were girls. Patients were admitted to hospital with abdominal pain (60,1%), nausea (9,5%), retrosternal burn (2%). A significant relationship was found between H.pylori intensity and inflammation (p<0.001). The sensitivity of stool H.pylori antigen test was 21.4%. DISCUSSION AND CONCLUSION: In pediatrics, H. pylori infection may be presented with nonspecific symptoms such as abdominal pain and nausea. Invasive tests are necessary for diagnosis.